Effect of Glycerol Concentration on Freezability of Buck Semen - MOHANTY, D N; GIRI, S C; BARIK, A K (The Indian Journal of Animal Reproduction, 2023)
Thirty six ejaculates from 6 Black Bengal bucks were diluted at the rate of I: IO in TEYCAFG (TrisEgg Yolk-citric acid Fructose Glycerol) extender having 3 different toncentrations of glycerol TC (Totalg lycero l) 4.0. 6.4 & 9.0 percent. The semen was frozen in straws and stored for three months.The seminalcharacteristics were assessed at monthly intervals. The present investigation revealed that the motility,live sperm count and sperm abnormalities for 4, 6.4 and 9 per cent glycerol extenders at zero hour freezirt1were 37 .53 J: 0.28. 42.12 ± 0.31, 36.63 ± 0.3 5, 66.32 ± 1.15, 64.61 ± 0.70, 61.63 ± 0.68 and 8.21 ± 0.26,9.13 -t. 0.34 and I 0.27 ± 0.27, respectively. The motile sperm per cent was found to be the highest (39.14:l 0.29, 38.82 ± 0.33 and 38.42 ± 0.39) for TC 6.4 as.compared to TC 4.0 and TC 9.0 for the I", 2nd and 3'4months of storage . Further, it was observed that the live sperm percentage was highest in TC 4.0 (61.91 ±0.67. 60.25 ± 0.51 and 59.50 ± 0.64) for the first three months of storage, respectively as compared to TC6.4 and TC 9.0. Similarly, highest percentage of sperm abnormalities was encountered in TC 9.0 (12.30 ±0.31. 13 .33 ± 0.32 and 14.15 ± 0.28) against the corresponding values for TC 6.4 and TC 4.0 for the threemonth s of obse rv at ion .
Keywords: Glycerol; TRIS; Freezing; buck